2016
DOI: 10.1371/journal.pone.0154064
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Clinical Outcomes between Drug Eluting Stents and Bare Metal Stents in Patients with Insulin-Treated Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis of 10 Randomized Controlled Trials

Abstract: BackgroundSeveral studies have shown Drug Eluting Stents (DES) to be better compared to Bare Metal Stents (BMS) in patients with type 2 Diabetes Mellitus (T2DM). Since, the adverse clinical outcomes in patients with Insulin-Treated Type 2 Diabetes Mellitus (ITDM) implanted with DES and BMS have not been previously studied, we aim to compare the clinical outcomes in similar patients with cardiovascular diseases, treated with DES and BMS.MethodsRandomized Controlled Trials (RCTs) comparing patients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Moreover, insulin treatment by itself was shown to be associated with significantly worse cardiovascular outcomes after PCI compared to non-insulin treated diabetes [ 25 , 26 ]. Nevertheless, compared to bare metal stents, drug eluting stents were shown to be associated with a significantly lower rate of repeat revascularization, without any increase in myocardial infarction or mortality in patients with insulin treated diabetes, during a follow up period of 1 year [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, insulin treatment by itself was shown to be associated with significantly worse cardiovascular outcomes after PCI compared to non-insulin treated diabetes [ 25 , 26 ]. Nevertheless, compared to bare metal stents, drug eluting stents were shown to be associated with a significantly lower rate of repeat revascularization, without any increase in myocardial infarction or mortality in patients with insulin treated diabetes, during a follow up period of 1 year [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate and long-term clinical outcomes of DES and bare-metal stents in diabetic population have already been investigated through the best of the study designs -randomized control trials and prospective registries. [17][18][19] One of the other important 300-patient randomized ESSENCE-DIABETES trial succeeded in showing non-inferiority of Everolimus-eluting stents (EESs) compared to first-generation sirolimus-eluting stents with respect to angiographic late lumen loss (LLL) at 8 months with no significant difference in clinical outcomes at 1 year, although the trial was not powered to show a statistical difference with respect to the latter follow ups. 20 Though the study was a prospective trial assessing MACE at the interval of 12 months only, the event rate was little higher (5.3% with SES) than current study in the diabetic patients (4.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DES provide better clinical outcomes compared to BMS. 1 Thus, an analysis that compares CABG to PCI with studies that include BMS would bias against the potential benefits of PCI. In a similar way, conduit selection can impact CABG outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For PCI, the use of drug eluting stents (DES) significantly reduce the restenosis rate and improve survival. 1 For CABG, the use of multiple instead of single arterial grafts (MAG vs SAG respectively) lead to better patency rate and possibly improved clinical outcome. 2 In this meta-analysis, we compare the contemporary therapeutic options for the treatment of patients with multiple vessel disease: PCI with DES, vs MAG CABG and SAG CABG.…”
Section: Introductionmentioning
confidence: 99%